Contracultura e resistência democrática: o Movimento dos Escritores Independentes de Pernambuco – 1980/1988. - Costa, Luiz Augusto Andrade da (2023)
This research proposes to analyze the history of the Pernambuco Independent Writers Movement (1980-1988), a group of men and women who, with poems and verses, broke with the limits imposed by the publishing market, censorship and aesthetic canons. of poetic writing. The expressive production of the Movement, in its handmade format of newspapers, fanzines, books and booklets; the interviews and testimonies of members, critics and contemporary journalists, as well as the articles published in the two main state newspapers in circulation at the time (Jornal do Commercio and Diário de Pernambuco) were our documentary bases. Taking the group as a striking manifestation of counterculture in the state, we place their artistic productions as one of the most important literary expressions in Pernambuco, influencing later generations of poets with their deliberately marginal aesthetics and behavior.